The mechanism of H2O in the superheated steam affecting the quality of in-situ pyrolysates of oil shale kerogen: Part B-favorable conversion of residues. (1st April 2023) - Zhao, Fumin; Li, Bao; Che, Daochang; Liu, Shengyu
Graphical abstract: Highlights: Residues were obtained by python codes to investigate aromaticity and porosity. Numbers of the broken CO, CN and CS bonds of pyrolysis systems were given. The H2 OSS involved products and typical pathways of residues were presented. The H2 OSS enhanced decomposition of residues during the initial BLK pyrolysis. BLK induced decomposition of H2 OSS which participated in pyrolysis reactions. Abstract: In this work, ReaxFF molecular dynamics (MD) simulation was applied to elucidate the enhancement effect of superheated steam on the conversion of residues into shale oil and gas during the initial pyrolysis of Barkol kerogen (BLK), and the corresponding mechanism was revealed. The weight loss rate (DTG) of BLK pyrolysis obtained from ReaxFF MD simulation agreed well with that form thermogravimetric experiment. Reaction pathways of the H2 OSS molecules (SS refers the superheated steam) and partial C40+ obtained from the extracted residues were analyzed. The results indicate that H2 OSS facilitated the conversion of residues to oil and gas in aspects of yield, heteroatomic removal rate, number of broken bonds of CC, CN, CS, distribution of carbon number of C40+, aromaticity and porosity. And this enhancement effect of H2 OSS is attributed to decomposition of H2 OSS molecules with inducement of kerogen and participation of H2 OSS as reactants in reactions during the initial pyrolysis of BLK. Analysis of typical reaction pathways shows that H2 OSS molecules were involved in disintegration of CC, CN, and CS bonds, shedding of aromatic substituents, ring-opening of aromatic heterocycles, removing aromatic heteroatoms, and further conversion of aromatics into aliphatics. These chemical reactions increase the porosity and pore connectivity of residues. Simultaneously, H2 OSS expansion promoted the deformation of the kerogen carbon skeleton, resulting in initial increase of porosity of kerogen. In addition, the mechanism of further conversion of aromatics to aliphatics for steam-pyrolytic residues was given. This paper provides theoretical guidance for in-situ conversion process (ICP) of kerogen with the superheated steam injection in the further understanding mechanism of H2 OSS on initial pyrolysis of kerogen and corresponding catalyst development and preparation.